Methodology of New Urbanism - Domińczak, Michał (Lodz University of Technology Press, 2024)
"The primary purpose of this paper is to present in detail the methodology of urban planning, which is characteristic of the ideological trend known in modern urbanism as New Urbanism and appearing in Poland most often under the name “Nowa Urbanistyka,” “Nowy Urbanizm,” or just “New Urbanism”1. Methodology is defi ned as ‘a system of methods used in a particular area of study or activity’. The methodology of the New Urbanism movement described in this work includes a set of principles and ways of implementing the ideas defi ned by the Charter of the New Urbanism, the decalogue of the movement. Thus, it is formed primarily by principles of urban design and ways of executing planning documents and creating local laws, but also by methods of implementing the legislative process, including conducting urban planning workshops (charettes) as part of public participation in urban planning. Part of the methodology presented in this way, in my opinion, is also “selling” the idea of good urbanism, which includes many factors usually neglected by the scientifi c community but especially appreciated by practitioners. [...]"
Cover design: Andrzej Gawęda
Graphic design and typesetting: Andrzej Gawęda
Translators: Wojciech Okoń, Michał Domińczak
Keywords: New Urbanism; charrette; SmartCode; architecture; Nowa Urbanistyka; architektura; charrette; SmartCode